Evaluation of the Implementation of the Stunting Management Program in Pusong Baru Village Banda Sakti District Lhokseumawe City - Anggi Pradini; Ti Aisyah; Mauludi Mauludi; Ferizaldi Ferizaldi; Murniati Murniati (Universitas Pahlawan Tuanku Tambusai, 2025)
This research is entitled “Evaluation of the Implementation of the Stunting Management Program in Pusong Baru Village, Banda Sakti District, Lhokseumawe City”. The background of this study is the high prevalence of stunting in the area. The objective is to evaluate the implementation of the program and identify inhibiting factors in stunting prevention. The study applied a descriptive qualitative method with data collected through observation, interviews, and documentation. The analysis was carried out using Theodoulou and Kofinis’ policy evaluation theory, which includes process, outcome, and impact evaluation. The findings indicate that, in terms of process, the program has been implemented through interventions targeting adolescent girls, pregnant women, and toddlers. Activities include iron and folic acid supplementation, nutrition education, growth monitoring at community health posts, and provision of supplementary food. In terms of outcomes, there has been an improvement in nutritional awareness, though uneven due to limited access to health posts and low participation of mothers and children. Meanwhile, the long-term impact remains less significant, as stunting rates are still relatively high. Barriers to implementation include limited resources, ineffective management, and inadequate infrastructure. Therefore, more optimal, integrated, and sustainable strategies are required to ensure the program reaches all target groups and successfully reduces stunting in New Pusong Village.